Application of traditional Chinese medicine in film drug delivery system - Li, Qianhang; Luo, Feng; Jiang, Pingnan; Feng, Chenxi; He, Feifei; Dong, Lina; Xu, Delin; Shi, Junhua (Frontiers in Pharmacology, 2022)
Film drug delivery systems have the advantages of precise administration, simple process and easy portability, compared with other traditional drug delivery systems such as tablets, capsules, syrups, ointments, etc. The traditional Chinese medicine (TCM) are normally developed in four categories of film agent like patch film, coating, spray film and gel film, which are applied to the treatment of oral ulcers, chronic diseases of lower limbs, burns, scalds, gynecological disease and body care. So the TCM film has great research value and prominent market prospect. In this review, we summarized the research progress of the material composition, pharmaceutical production, clinical application and pharmacology mechanism of various TCM film agents. It may provide a comprehensive reference for further development and utilization of TCM film agents.